Social creativity of early primary school pupils and behavioral patterns in school conflicts - Vlah, Nataša (Array, 2020)
According to the theory of conflict resolution, in the school, as an educational institution, systematic influences on constructive social behaviors and quality choices are possible. The study aimed to determine the relation-ship between the creative potential of early primary school pupils and their patterns of behavior in school conflicts. Early primary school pupils (N = 73; 55.1% girls) participated in the research by solving the EPoC-SOC test of po-tential social creativity. Their teachers (N = 16; 38-60 years; 96% women) assessed three patterns of pupil behavior (winning, avoiding, and cooperation). Non-standardized results were used to assess divergent-exploratory thinking as well as convergent-integrative thinking in tasks with dyad social relations and group tasks. Correlation analysis found only a statistically significant negative association between the avoidance pattern and achievement on the tasks of convergent-integrative social creativity. The obtained results suggest the need for further research on the relationship between pupils’ social competency and behavior in conflicts.